THE THE DIFFERENCES OF ORIGAMI AND COLORING GAMES ON THE FINE MOTOR DEVELOPMENT OF PRESCHOOL GIRLS IN TK GRAND BALI BEACH SANUR - Ameondari, Ni Made; Winaya, Made Niko; Adiputra, Luh Made Indah Sri Handari; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Increase motor development can be done by providing a stimulus. Good stimulus will stimulate children's development in various aspects. With the aim to know the difference between origami and coloring in improving fine motor development of children. Draft Pre and Post Test Two Group Design. Sampling using simple random sampling. These samples included 32 people and data collection is done with Fine Motor Skills Tests. The results showed an increase fine motor development in group 1 amounted to 70.31±3.754 and in group 2 an increase of 71.44±5.046. Independent Sample test showed no significant difference between group 1 and 2 p = 0.894 (p> 0.05). It was concluded that the origami and coloring equally well to improving fine motor development of children. Keywords : Fine motor, origami, coloring.